Government bond risk premia and the cyclicality of fiscal policy - Kai Christoffel; Ivan Jaccard; Juha Kilponen (European Central Bank (ECB), 2011)
We introduce a specification of habit formation featuring non-separability between consumption and leisure into an otherwise standard New Keynesian model. The model can be estimated with standard Bayesian techniques and the bond pricing implications are evaluated using higher-order approximations. The model is able to reproduce a sizeable risk premium on long-term bonds and the cyclicality of fiscal policy has an impact on the bond premium that is quantitatively important. Technology, government spending, and mark-up shocks are the main drivers of the time-variation in bond premia.
Keywords: E5; E6; G1; 330; bond risk premium; DSGE Models; Fiscal Policy; monetary policy